Tectonic stability of the Nanpu sag: Evidence from temporal and spatial characteristics of seismic activity - ZHANG Yang; SHANG Lin; WANG Miao; WU Haitao; DUAN Bin (Dizhi lixue xuebao)
Objective  The evaluation of regional tectonic stability plays a crucial role in the planning and construction of major projects. Given that the Nanpu sag is the site for China's first offshore gas storage facility, its tectonic stability is naturally a focal point of concern.   Methods  Based on historical seismic data for the region, this study summarizes the spatiotemporal distribution of seismic activities in the Nanpu sag and its surrounding areas. It analyzes the rupture modes of the Tangshan−Hejian−Cixian fault zone and the Zhangjiakou−Penglai fault zone, and explores the tectonic stability of the Nanpu sag.   Results  The results indicate that the Nanpu sag is a relatively stable "safe island" near active tectonic zones. Regionally, stress accumulated around the periphery of the Nanpu sag is mainly released through the activity of faults such as the Luanxian−Laoting and Baodi−Ninghe faults, and the influence of the seismic activity at the periphery on the interior of the Nanpu sag is limited. Internally, a large-scale creep-dominated extensional deformation system has developed within the Nanpu sag.   Conclusion  Given the current tectonic stress background, only a small magnitude of stress accumulation is required to trigger unstable sliding of pre-existing normal faults within the Nanpu sag. This suggests that stress cannot accumulate over long time scales, and thus the interior of the Nanpu sag lacks conditions for the occurrence of major earthquakes.